Analysis of the correlations between changes in posterior segment and anterior chamber segment after implantable collamer lens implantation in highly myopic patients - Yifei Peng; Lu Xiong; Haokun Qu; Yang Liu; Zheng Wang (BMC Ophthalmology)
Abstract Purpose To evaluate the impact of Implantable Collamer Lens (ICL) implantation on anterior chamber angle parameters and posterior segment structures in highly myopic eyes and explore potential correlations between these changes. The study aimed to assess alterations in superficial and deep vessel density (SVD, DVD), foveal avascular zone (FAZ) area, and retinal nerve fiber layer (RNFL) thickness to clarify the safety profile of ICL implantation. Methods Prospective observational study, included 36 highly myopic eyes undergoing ICL implantation in surgery group and 23 non-surgical control eyes in non-surgery group. Anterior chamber parameters were assessed using AS-OCT, and posterior segment changes, including SVD, DVD, FAZ, and RNFL, were evaluated using OCT and OCTA preoperatively and at intervals up to 3 months postoperatively. Statistical analyses included paired t-tests, Wilcoxon tests, and Spearman correlation. Results ICL implantation significantly improved uncorrected distance visual acuity (UDVA) (p < 0.01). Anterior chamber depth (ACD) and angle parameters, such as AOD and TISA, decreased initially but stabilized by 3 months. SVD and DVD showed early postoperative fluctuations, returning to baseline by 3 months, while the FAZ area and subfoveal choroidal thickness remained stable. Significant correlations were identified between anterior segment narrowing and posterior vascular changes, particularly in the pericentral region. Conclusions ICL implantation effectively and safely corrects high myopia, with stable anterior and posterior structural changes by 3 months. Transient vascular density fluctuations correlated with anterior chamber angle alterations, highlighting the need for long-term studies to further understand these dynamics and ensure retinal safety postoperatively. Trial registration The study was approved by the ethics committee of Aier Eye Hospital, Jinan University (No. GZAIER2023IRB25; China Clinical Trial Record No. MR-44-24-009241).